PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, PELATIHAN DAN MOTIVASI TERHADAP KINERJA GURU SE KECAMATAN PARUNGPANJANG: Kepemimpinan Kepala Sekolah, Pelatihan dan Motivasi terhadap Kinerja Guru - PAHRUROJI PAHRUROJI (LPPM Institut Nida El-Adabi, 2023)
The purpose of this study was to determine the effect of Principal’s Leadership (variable X1), Training (variable X2), Motivation (variable X3) and Teacher performance (variable Y) at Vocational Schools in Parungpanjang. The design of this hypothesis is Ho: rxy = 0, that there is a significant influence between X and Y and Ha: rxy ≠ 0, that there is a significant influence between x and y. Hypothesis testing is done by comparing the value of t count (th) correlation coefficient x and y (rxy) with the critical value t table (tt): if t count> t table then Ho is rejected, Ha is accepted and vice versa if t count <t table then Ho is accepted , H1 rejected. The research method used by the author is a descriptive quantitative approach. The sampling technique uses simple random sampling. The data collection method used is the questionnaire method. Processing data using the SPSS Version 23 program. The results of this study found the Principal’s Leadership (X1) with a calculated t value, it is known that the value of t count is 1.161< t table 1.983 and the significance level is smaller, it is known that the significance value is 0.249> 0.05, H0 is rejected and H1 is accepted. Training (X2) with the value of t count, it is known that the value of t count is 2,516< t table 1,983 and the significance level is smaller, it is known that the significance value is 0,013> 0.05, then H0 is rejected and H1 is accepted. Motivation (X3) with a calculated t value, it is known that the value of t count is 5.705> t table 1.983 and the significance level is smaller, it is known that the significance value is 0.000 < 0.05, then H0 is rejected and H1 is accepted. Thus it can be concluded that the Effect of Principal’s Leadership (X1), Training (X2), Motivation (X3) simultaneously has a positive and significant effect on teacher performance influenced by other variables outside of this study. Test F the influence of the principal’s leadership (X1), Training (X2), Motivation (X3) on Teacher performance (Y), known F-count value of 12,595 > F-table 2.432 and significance value of 0,000 < 0.05, then H1 is accepted and Ho is rejected .